Bitcoin sebagai Alat Pembayaran Online dalam Perdagangan Internasional - Dwikky Ananda Rinaldi; Mokhamad Khoirul Huda (Faculty of Law Hang Tuah University, 2016)
The growth of national economy encourages a significant change in the financial sector, especially a means of payment. Starting from the barter, the means then changes to be the goods or commodities, and finally the metal and paper as a raw material of money. The form of money as a means of payment continuously changes namely in the form of checks and transfer form that allow payment through transferring funds from the account balances among financial institutions, especially the banks. The economic need continuously grows so that it shifts the ways of trade transactions from conventional to internet based one that is known as e-commerce. One of the International online payment means required in an e-commerce transaction is Bitcoin. Bitcoin is an electronic coin that uses a system of peer-to-peer network that is open source. Bitcoin is not a virtual coin and not the legal means of payment in Indonesia. The legal means in Indonesia is the rupiah. It has been described in Article 1 section (2) of Act No. 7 of 2011 on Currencies that the the coin used for payment transactions in Indonesia is the rupiah.